Introducing Kuhn et al.’s Paper“Informatics and Medicine: From Molecules to Populations” and Invited Papers on this Special Topic - Kulikowski, C. A. (Methods of Information in Medicine, 2008)
Objective: To introduce the paper by Kuhn et al. “Informatics and Medicine: From Molecules to Populations” and the papers that follow on this special topic in this issue of Methods of Information in Medicine, which opens a debate on the Kuhn et al. paper’s assertions by an international panel of invited researchers in biomedical informatics.Method: An introductory summary and comparative review of the Kuhn et al. paper and the debate papers, with some personal observations.Results: The Kuhn et al. paper makes a strong case for interdisciplinary education in biomedical informatics across institutions at the graduate level, which could be strengthened by analysis of previous relevant interdisciplinary experiences elsewhere, and the challenges they have faced, which point to more pervasive and earlier-stage needs for both education and practice bridging the research and healthcare communities.Conclusions: The experts debating the Kuhn et al. paper strongly and broadly support the key recommendation of developing graduate education in biomedical informatics in a more comprehensive way, yet at the same time make some incisive comments about the limitations of the “positivistic” and excessively technological orientation of the paper, which could benefit from greater attention to the narrative and care-giving aspects of health practice, with more emphasis on its human and social aspects.
Keywords: Informatics; medicine; interdisciplinary education; molecules to populations; genotype to phenotype; clinome; narrative medicine; evidence-based medicine